1999
DOI: 10.1557/jmr.1999.0554
|View full text |Cite
|
Sign up to set email alerts
|

Strain gradient plasticity effect in indentation hardness of polymers

Abstract: Plasticity in material is typically described as a function of strain, but recent observations from torsion and indentation experiments in metals suggested that plasticity is also dependent on strain gradient. The effects of strain gradient on plastic deformation in thermosetting epoxy and polycarbonate thermoplastic were experimentally investigated by nanoindentation and atomic force microscopy in this study. Both thermosetting and thermoplastic polymers exhibited hardening as a result of imposed strain gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
122
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(132 citation statements)
references
References 7 publications
9
122
0
1
Order By: Relevance
“…Such elevated hardnesses at small indentation depths have also been observed in polymers [Briscoe et al 1998;Chong and Lam 1999;Tjernlund et al 2004;Lim and Chaudhri 2006; but, in comparison to metals, for polymers these effects are not well understood. An understanding of size-dependent deformation behavior is important not only for small components in MEMS/NEMS (micro/nano-electromechanical systems), but also for the development of advanced material systems and composite materials with small material phases and other applications such as sealants, gaskets [Tan et al 2007], and adhesives [Han et al 2007b].…”
Section: Introductionmentioning
confidence: 90%
“…Such elevated hardnesses at small indentation depths have also been observed in polymers [Briscoe et al 1998;Chong and Lam 1999;Tjernlund et al 2004;Lim and Chaudhri 2006; but, in comparison to metals, for polymers these effects are not well understood. An understanding of size-dependent deformation behavior is important not only for small components in MEMS/NEMS (micro/nano-electromechanical systems), but also for the development of advanced material systems and composite materials with small material phases and other applications such as sealants, gaskets [Tan et al 2007], and adhesives [Han et al 2007b].…”
Section: Introductionmentioning
confidence: 90%
“…Other measurements evaluate the material length scale parameter of single crystal and polycrystalline copper to be 12 and 5.84 μm, respectively (McElhaney et al, 1998;Nix and Gao, 1998). Also, the size-dependent behavior has been detected in some kinds of polymers (Chong and Lam, 1999). For hardness measurement of bulk gold, it is found that the plastic length scale parameter (for indentation test and hardness behavior) of Au increases from 470 nm to 1.05 μm with increasing the Au film thickness from 500 nm to 2 μm (Cao et al, 2007).…”
Section: Using Various Approachesmentioning
confidence: 99%
“…The experiments conducted on the microstructures subjected to different loading conditions have revealed their size-dependent behavior (Nix 1989;Fleck et al 1994;Ma and Clarke 1995;Vardoulakis et al 1998;Stolken and Evans 1998;Chong and Lam 1999;Lam et al 2003;and Colton 2005). When the dimensions of a structure are on the order of microns or submicrons, it R. Ansari is necessary to consider internal material length scale parameters in order to predict its mechanical behavior.…”
Section: Introductionmentioning
confidence: 99%